10 Years of Toxicogenomics section in Frontiers in Genetics: Past discoveries and Future Perspectives - Ruden, Douglas M. (Frontiers in Genetics, 2022)
The year 2021 is the tenth anniversary of the founding of the Frontiers in Genetics journal and the Frontiers in Toxicogenomics specialty section of this journal. I am the founding, and currently sole, Specialty Chief Editor of Frontiers in Toxicogenomics. I am also one of 9 Specialty Chief Editors of Frontiers in Toxicology, a new Frontiers in Genetics specialty journal founded in 2011, when the associate editors and I added a new specialty journal to expand the type of articles that can be submitted and reviewed. Today, we have published over 138 articles in Frontiers in Toxicogenomics and have over 370 Editors including 90 Associate Editors and 280 Review Editors. Our impact factor was initially approximately 2.5 when it was first listed in PubMed in 2015 and has risen steadily to its current value of 4.274. In this overview of the first decade of Frontiers in Toxicogenomics, I discuss the top 5 articles with the highest Scopus citations, which were all written in the first few years of the journal. Finally, I discuss where the journal will go to advance the field of toxicogenomics in the future.